The Scope and Autonomy of Personal Narrative. (January 2017) - Ingraham, Chris
The work of Carol Berkenkotter and others who have expanded the realm of personal narrative studies over the past several decades would not have been possible without the pioneering efforts of those who first brought the study of narrative to nonliterary discourses. By revisiting what personal narratives were to these pioneers—working outward from William Labov in particular—this article considers how the early expansion of the field helps us to understand the far wider expansion of multimodal personal narrative today. In doing so, I suggest that understanding the notion of a personal narrative requires a twofold commitment to inquiry: first, about what makes it narrative ; and second, about what makes it personal . These commitments hinge on two crucial junctures, what I call the problem of scope and the problem of autonomy. Framed as questions, the former asks, When does a narrative begin and end? The latter asks, Whose narrative is it? This recuperative essay shows that the heuristics of scope and autonomy can be useful ways to think about the ongoing complexities of personal narrative and its analysis.